BOARDGAME SEBAGAI MEDIA KONSELING UNTUK MELATIH SELF REFLECTION - Irwanto Gani (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam, 2022)
Fun is a fundamental principle of play. Through play we can inspire players to think about the situation they are in and what they can do about it, which will help in the process of self-reflection. To produce self-reflection, the characters in the game must have a relationship with the player so that the feelings experienced by the player can be reflected. This research uses a qualitative approach to find out facts in the field regarding the ability to self-reflect using board games.